Effect of Ethanol Extracts from Persea americana Leaves on HSC-3 Proliferation - Tessalonica, Svetlana; Roeslan, Moehamad Orliando (Indonesian Dental Association, 2020)
Introduction: Oral cancer has one of the highest death rates of all cancer types due to lack of treatment. Persea americana leaves consist of phenolic compounds that are known to have anticancer effects to inhibit the proliferation of human squamous carcinoma (HSC-3) cell lines. Ethanol extracts from P. americana leaves can inhibit the cell cycle in the G1/S and G2/M phases to give the cells time to repair damaged DNA. Objective: The aim of this study was to investigate the effect of ethanol extracts from P. americana leaves on HSC-3 proliferation. Methods: This study was conducted using experimental research and in vitro laboratory testing. Groups of extract consisted of four concentrations (100%, 50%, 25%, and 10%). Cytotoxic activity of the extracts was measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide tetrazolium (MTT) assay. Result: P. americana leave ethanol extracts with concentrations of 100% had a significant difference (p <0.05) compared to negative control. Conclusion: Ethanol extracts from P. americana leaves could inhibit HSC-3 proliferation.